Gender issues and sexuality essential primary sources - Lerner, K. Lee; Lerner, Brenda Wilmoth; Lerner, Adrienne Wilmoth (Social issues primary sources collection, 2006)
A focus on leading social issues of the 19th, 20th, and 21st centuries. Each title contains approximately 175 full or excerpted documents---speeches, legislation, magazine and newspaper articles, essays, memoirs, letters, interviews, novels, songs, and works of art---as well as overview information that places each document in context.